2005
DOI: 10.1063/1.2038768
|View full text |Cite
|
Sign up to set email alerts
|

Applications of a time correlation function theory for the fifth-order Raman response function I: Atomic liquids

Abstract: Multidimensional spectroscopy has the ability to provide great insight into the complex dynamics and time-resolved structure of liquids. Theoretically describing these experiments requires calculating the nonlinear-response function, which is a combination of quantum-mechanical time correlation functions R5(t1,t2) was expressed with a two-time, computationally tractable, classical TCF. Writing the response function in terms of classical TCFs brings the full power of atomistically detailed molecular dynamics to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
15
0
Order By: Relevance
“…16,27 The nature of the stability matrix 39,40 and the phenomenological simulation method to calculate the fifth-order signals such as the Langevin treatment have been investigated. [41][42][43][44] Since the experimental results are limited to the case of CS 2 , the theoretical models and the phenomenological simulation methods mentioned above have to be justified by comparing the signal accurately calculated from the MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…16,27 The nature of the stability matrix 39,40 and the phenomenological simulation method to calculate the fifth-order signals such as the Langevin treatment have been investigated. [41][42][43][44] Since the experimental results are limited to the case of CS 2 , the theoretical models and the phenomenological simulation methods mentioned above have to be justified by comparing the signal accurately calculated from the MD simulations.…”
Section: Introductionmentioning
confidence: 99%
“…31 The effect of the nonlinear polarizabilities in real systems, i.e., liquid Xe, CS 2 , and water, was first analyzed by using normal mode description. [42][43][44][45][46][47][48][49] In particular, Denny and Reichman successfully reproduced the 2D-Raman signal of liquid Xe based on the mode coupling theory by using the factorizing 32 Ma and Stratt found that a clear echo signal of the 2D-Raman response exists in the instantaneous normal mode description of liquid Xe, but disappears when the full molecular dynamics ͑MD͒ calculation is employed.…”
Section: Introductionmentioning
confidence: 99%
“…[48][49][50][51][52] Their development retreats to the quantum mechanical analogue of Eq. (A1) (with timedependent quantum mechanical operators and commutators in the place of classical dynamical variables and Poisson brackets) expressed in terms of real and imaginary parts of quantum time correlation functions, builds in a relationship between those parts valid for harmonic systems, and then identifies the real part of the quantum time correlation function with its classical analogue.…”
Section: (A4)mentioning
confidence: 96%
“…Some of these have made use of generalized-Langevin-equation 40,41 and modecoupling 42-47 frameworks, but there has also been a novel formulation in which the classical results have been predicted based on approximations to the quantum mechanical analogue. [48][49][50][51][52] We propose yet another approach here. What turned out to be key for our purposes was the realization that for the kinds of problems of interest in solvation spectroscopy, the time scales T and t are usually going to be widely separated.…”
Section: B Hybrid Instantaneous-normal-mode/molecular Dynamics Evalumentioning
confidence: 98%